Suitability of herring gulls (Larus argentatus) as indicators for detecting intertidal bivalve beds in the Wadden Sea - Leonie Enners (Elsevier, 2021)
Germany is an EU member state and is thus obliged to monitor and protect its marine and coastal areas in the context of international treaties (e.g. EU Marine Strategy Framework Directive, EU Natura2000 directives, Trilateral Monitoring and Assessment Programme, OSPAR) to achieve the good environmental status (GES). Suitable indicators thus need to be developed to assess the status of relevant ecosystems. Intertidal bivalve beds belong to the most productive habitats in the shallow coastal waters of the Wadden Sea but are highly dynamic and difficult to monitor. Extensive benthos and sediment sampling are required to study their development and distribution. We therefore evaluated the suitability of herring gulls (Larus argentatus) as a bioindicator species for monitoring these habitats. As flexible and opportunistic top-predators, herring gulls prefer to forage on intertidal flats and feed on bivalves (Cerastoderma edule, Mytilus edulis, Ensis leei) and crustaceans, with intertidal habitats near the breeding colony preferred during the incubation period. We used state of the art tracking devices to analyse habitat selection by herring gulls, and assessed how this was driven by biotic and abiotic factors. We then designed a habitat model to predict the occurrence of intertidal bivalve beds for directed monitoring, based on GPS logger data from herring gulls and hydrodynamic data. Both methods showed high correlations of herring gull foraging patterns with bivalve biomass and inundation time, depending on the distance from the breeding colony. The movement patterns of herring gulls clearly mirrored intertidal bivalve distributions. These results showed that combining GPS-logger data for top-predators, such as birds, with environmental data has great potential for monitoring and assessing the GES. We propose that herring gulls may be used as an indicator to locate bivalve beds in the Wadden Sea and to detect changes in the food web.